Experimental study on the correlation between hill direct seeding rate and field seedling rate of typical rice varieties in cold areas - Tang, Han; Jiang, Yeming; Xu, Changsu; Zhou, Wenqi; Wang, Qi; Wang, Yijia (International Journal of Agricultural and Biological Engineering, 2021)
In order to examine the relationship between the seeding rate of a hill-direct-seeding machine and seedling rate in field, six rice varieties typical for cold areas were selected to conduct the indoor germination tests and field seedling experiment using a hill-direct-seeding machine. Indoor germination and field seedling tests were performed to study the correlation among the mechanical precision seeding process, machine seeding rate and field seedling rate. The results showed that the indoor germination rates were higher than 90%. The series of spoons was adaptable to the hill-direct-seeding process. The number of seeds was 28-30, 18-20 and 8-10 grains/hill. The field seedling rates were higher than 85%. The rice variety of Suijing-18 achieved the best field seedling rate, and the highest seeding rate was 18-20 grains/hill, while the average field seedling rate was 94.25%. On this basis, the action law of the hill-direct-seeding machine and the main factors influencing the field seedling rate were analyzed. Mechanical vibration resulted in a higher average seeding rate of the middle seed metering device of the hill-direct-seeding machine than that of both ends. The force between the seed spoons and rice seeds mechanically damaged the seed buds, resulting in the actual field seedling rate being lower than the ideal indoor germination rate. The experimental results can provide a reference for the selection of typical direct seeding rice varieties, the improvement of key components of hill-direct-seeding machines, and the promotion of agronomic models.Keywords: cold areas, rice, machine, hill-direct-seeding, seeding rate, seedling rateDOI: 10.25165/j.ijabe.20211405.6020Citation: Tang H, Jiang Y M, Xu C S, Zhou W Q, Wang Q, Wang Y J. Experimental study on the correlation between hill direct seeding rate and field seedling rate of typical rice varieties in cold areas. Int J Agric & Biol Eng, 2021; 14(5): 63–71.